Invariant Natural Killer T Cells Play a Role in Chemotaxis, Complement Activation and Mucus Production in a Mouse Model of Airway Hyperreactivity and Inflammation. - Piia Karisola; Maili Lehto; Pia Kinaret; Niina Ahonen; Rita Haapakoski; Minna Anthoni; Masaru Taniguchi; Henrik Wolff; Anne Puustinen; Harri Alenius (PLoS ONE, 2015)
CD1d-restricted invariant natural killer T (iNKT) cells play a critical role in the induction of airway hyperreactivity (AHR). After intranasal alpha-galactosylceramide (α-GalCer) administration, bronchoalveolar lavage fluid (BALF) proteins from mouse lung were resolved by two-dimensional differential gel electrophoresis (2D-DIGE), and identified by tandem mass spectroscopy. A lack of iNKT cells prevented the development of airway responses including AHR, neutrophilia and the production of the proinflammatory cytokines in lungs. Differentially abundant proteins in the BALF proteome of α-GalCer-treated wild type mice included lungkine (CXCL15), pulmonary surfactant-associated protein D (SFTPD), calcium-activated chloride channel regulator 1 (CLCA1), fragments of complement 3, chitinase 3-like proteins 1 (CH3LI) and 3 (CH3L3) and neutrophil gelatinase-associated lipocalin (NGAL). These proteins may contribute to iNKT regulated AHR via several mechanisms: altering leukocyte chemotaxis, increasing airway mucus production and possibly via complement activation.